Effect of fungicide treatment and nitrogen fertilisation on the yield of two breeding types of winter oilseed rape cultivars - Wójtowicz, Marek; Franciszek Wielebski; Wójtowicz, Andrzej; Jajor, Ewa; Korbas, Marek (Emirates Journal of Food and Agriculture, 2023)
The effect of three fungicide treatment programmes and the level of spring nitrogen fertilisation on the seed yield of two types of cultivars of Brassica napus L. sown at two different seeding rates was studied in a field experiment. The subject of the study was an open-pollinated cultivar ‘Casoar’ and a restored hybrid cultivar ‘Visby’. Three plant protection programmes, two levels of spring nitrogen fertilisation (160 and 220 kg N⋅ha1), and two different seeding rates for each cultivar (‘Visby’—50 and 70 seeds⋅⋅m2; ‘Casoar’—60 and 80 seeds⋅m2) were included. The most intensive protection programme comprised three fungicide treatments: first in autumn at the six-leaves-unfolded stage—BBCH 16, second in spring at the stem elongation stage—BBCH 33, and third at the full flowering stage—BBCH 65. One of two less intensive programmes of plant protection included fungicide application in autumn at the sixleaves-unfolded stage—BBCH 16 and at the full flowering stage—BBCH 65, while the second included fungicide application in spring at the stem elongation stage—BBCH 33 and at the full flowering stage—BBCH 65. The effectiveness of the protection programmes and nitrogen fertilisation was influenced by the intensity of abiotic stress factors. The average yield from the plots protected against pathogens was significantly higher than that from the untreated plots. The increase of nitrogen fertilisation from 160 to 220 kg⋅ha1 also caused a significant increase of average seed yield. The yield of cultivar ‘Visby’ was higher and less dependent on the seeding rate compared to cultivar ‘Casoar’. Keywords: Winter oilseed rape; Cultivars; Disease control; Nitrogen fertilisation; Seeding rate; Sclerotinia sclerotiorum; Leptosphaeria spp.; Alternaria spp. Botrytis cinerea.